2022
DOI: 10.3389/fphys.2022.967661
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two stories: COVID-19 and disability. A critical scoping review of the literature on the effects of the pandemic among athletes with disabilities and para-athletes

Abstract: The still ongoing COVID-19 pandemic has dramatically impacted athletes, and, in particular, para-athletes and athletes with disabilities. However, there is no scholarly appraisal on this topic. Therefore, a critical scoping review of the literature was conducted. We were able to retrieve sixteen relevant studies. The sample size ranged from 4 to 183. Most studies were observational, cross-sectional, and questionnaire-based surveys, two studies were interventional, and two were longitudinal. One study was a tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 66 publications
0
17
0
Order By: Relevance
“…Therefore, in para-rowing, further studies are warranted involving a broad range of impairments and disabilities, with particular attention paid to spinal cord injury. Finally, although in recent years COVID-19 has dramatically impacted the Paralympic sport arena [ 53 ], there are no published studies investigating this topic, which deserves to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in para-rowing, further studies are warranted involving a broad range of impairments and disabilities, with particular attention paid to spinal cord injury. Finally, although in recent years COVID-19 has dramatically impacted the Paralympic sport arena [ 53 ], there are no published studies investigating this topic, which deserves to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Both recreational and elite athletes had to cope with uncertainty, regularly changing measures that impacted their training routines, and the cancelation of competitive events. Several studies indicated that the COVID-19 pandemic impacted athletes’ well-being and performance (e.g., Puce et al, 2022 ), but why some athletes suffered more than others remained unknown. Only one previous study looked at whether athletes’ ability to cope with the pandemic depended on their motivation ( Morbée et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, athletes’ need for relatedness was under threat, as isolation and keeping distance (e.g., from friends, family members, and teammates) were core aspects of the measures imposed to prevent the COVID-19 virus to spread. Finally, especially for Paralympic athletes, the disruption of the preparation for one of the most important competitive events of their career potentially hampered or undermined their competence satisfaction ( Puce et al, 2022 ). Moreover, given the postponement or cancelation of competitions, it was difficult for athletes to judge properly where they stood in terms of adjusting their intermediate goals compared to opponents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations